"Absolutely the worst drug I've ever seen": Risk, governance, and the construction of the illicit fentanyl "crisis". (November 2020) - Kennedy, Liam; Coelho, Madelaine
In this article, we analyze 1027 articles published in four newspapers in order to trace the construction of the fentanyl "crisis" across social contexts. Our analysis reveals that Chinese producers and Mexican cartels were censured for bringing this deadly substance into Canada and the United States as the number of fentanyl-related deaths and overdoses increased. Indeed, news media construct this "illicit" form of fentanyl as foreign and risky. We contend that this coverage diverts attention away from the consequences of the neoliberal policies that contribute to opioid use and plays an important role in stoking feelings of insecurity that justify a disconcertingly wide range of governing practices that aim to secure the homeland against external threats, advance the state's interests abroad, and discipline larger swaths of the population at home.